Lost and Found in Translation: Examining the English Version of Perahu Kertas - Maharani, Ni Made Dinda; Duriga, Talitha Sevrilla; Barus, Elsika Br.; Aryani, I Gusti Agung Istri (JETLEE: Journal of English Language Teaching, Linguistics, and Literature, 2025)
Translation plays a key role in conveying meaning, context, and cultural relevance across languages. This study aims to analyze the translation strategies used in the Indonesian novel “Perahu Kertas” (SL) and its English version “Paper Boats” (TL), based on Baker’s translation theory. The research focuses on the application of all eight of Baker’s translation strategies. Using qualitative methods, the researcher compares the source and target texts to identify how these strategies were applied in both texts. The findings reveal that seven out of the eight strategies were used in the novel, with translation by illustration being absent. The three dominant strategies found were translation by paraphrase using related words, translation by omission, and translation by a more neutral/less expressive word, which prioritized meaning and appropriateness in the target language. This study provides valuable insights for translators and researchers in the translation field.